NEW AND CRITICAL MALESIAN PLANTS VII - A. J. G. H. KOSTERMANS (BRIN Publishing (Penerbit BRIN), 1965)
1. Anacardiaceao: Mangifera caesia Jack is combined with M. kemanga Bl. and 3 varieties are recognized: caesia, kemanga and wanji. 2. Newly described are: M. pajang and M. torquenda. 3. Lepidadenia seloang Miquel represents: Phoebe declinwta Bl. 4. New Lauraceae: Beilschmiedia glabra, B. dictyoneura, B. bangkae, B. raontanoides, B. rivularis; Endiandra ochracea, E. magnilimba. 5. In Meliaceae are newly described: Aphanamixis reticulosa, Lansium pedicellatum and L. sepalinum. 6. Sterculia minahassae Kds. is referred to Firmiana. F. philippinensis Kosterm. is reduced to synonymy.